Potential pyruvate and poly (3- hydroxybutyrate) production of halophiles bacteria isolated from Giao Thuy, Nam Dinh’s mangrove forest - Lan Anh, Hoang Thi; Tam, Luu Thi; Minh Hien, Hoang Thi Thi; Ha, Nguyen Cam; Thu, Ngo Thi Hoai; Kawata, Yoshikazu; Diep, Ngo Thi Hoa; Thuy, Nguyen Thanh; Hong, Dang Diem (Academia Journal of Biology, 2018)
Pyruvic acid (pyruvate) the most important α-oxocarboxylic acid, plays a central role in energy metabo-lism in living organisms. It is used mainly as a starting material in the biosynthesis of pharmaceuticals as well as employed in the production of crop protection agents, polymers, cosmetics and food additives. Four Gram-negative, moderately halophilic, pyruvate and poly (3-hydroxybutyrate)- producing strains were isolated from soil samples collected from mangrove forest at Giao Thuy, Nam Dinh province. Preliminary screening results showed that among fours strain, the ND7 strain was able to produce the highest bioplastic-poly (3-hydroxybutyrate) (PHB) and extracellular secretion of pyruvate, respectively, reaching 50.23% dry weight and 6.87 g/L after 60 hours of cultivation. When cultured in high alkaliphilic medium (pH 9.4), the pyruvate secretion increased significantly (21.02 g/L after 60 hours of cultivation). Based on the morphological, bio-chemical characteristics and nucleotide sequence analysis of partial 16S rRNA gene, the ND7 strain was iden-tified as Halomonas maura. The results allow us to conclude that ND7 strain is a potential target for the ex-ploitation of pyruvate in a larger scale